Cytochemical and mycrobicide activity of blood phagocytes in pulmonary tuberculosis patients - O. V. Filinyuk; N. A. Zemlyanaya; A. K. Strelis; O. I. Ourazova; O. V. Voronkova; N. M. Shevtsova; I. Ye. Yesimova (Бюллетень сибирской медицины, 2007)
Aimed at non-specific reactivity of the organism, cytochemical activity and microbicidal properties of blood neutrophils and peripheral blood monocytes were studied in 102 patients with drug-sensitive pulmonary tuberculosis before the treatment, after in-tensive phase of therapy and after stopping anti-tuberculosis therapy. Increased hydrolytic enzymes' activity of leucocytes, levels of non- cationic proteins and decreased levels of cellular glycogen and induced NBT-test were observed without their dependence on drug-sensitivity of mycobacterial tuberculosis before and during the treatment.. At the same time, content of lipids in neutrophils and monocytes undergoes different changes.